THE INFLUENCE OF ORGANISATIONAL CULTURE AND INTERNAL COMMUNICATION ON ORGANISATIONAL COMMITMENT THROUGH WORK ATTACHMENT AT THE CLASS II NON-TPI BANGGAI IMMIGRATION OFFICE - Agus Sumadi; Mashur Razak; Muh. Ashary Anshar (Yayasan Education and Social Center, 2026)
This study aims to analyze the influence of organizational culture and internal communication on organizational commitment through work attachment at the Class II Non-TPI Banggai Immigration Office. The study employs a quantitative approach using a survey method. The study population comprises all staff at the Class II Non-TPI Banggai Immigration Office, with a saturation sampling technique applied so that the entire population served as respondents. Data collection was carried out by distributing a questionnaire using a five-point Likert scale. Data analysis was performed using the Structural Equation Modelling-Partial Least Squares (SEM-PLS) method with SmartPLS 4 software. The results indicate that organizational culture has a positive and significant effect on job engagement and organizational commitment. Internal communication was also found to have a positive and significant effect on both job engagement and organizational commitment. Furthermore, job engagement has a positive and significant effect on organizational commitment. The mediation test results showed that job engagement positively and significantly mediates the effect of organizational culture on organizational commitment, as well as mediating the effect of internal communication on organizational commitment. These findings indicate that strengthening organizational culture and effective internal communication can enhance employees' job engagement, thereby increasing organizational commitment. Therefore, organizations need to strengthen the implementation of organizational cultural values, foster open and participatory internal communication, and create a working environment that enhances job engagement to support the sustainable achievement of organizational goals.